2009
DOI: 10.1002/ca.20815
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro morphometry of the human trachea

Abstract: Most morphometric studies of the human trachea have relied on plain radiographs with their attendant limitations. Reports using computed tomography (CT) have focused on the growing trachea or one particular dimension. The aim of this study was to document the morphometry of the adult trachea in vivo using high-resolution chest CT scans, supplemented by data from cadavers. Sixty anonymised high-resolution chest CT scans (aged 22-88 years, 40 males) were analyzed. Scans were performed using a standardized breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 17 publications
3
100
5
1
Order By: Relevance
“…In our study, the subglottic and tracheal dimensions in females were comparatively and statistically less than males this is in agreement with most of the other studies [6,8,11]. We have observed that the trachea being a dynamic structure the shape of the trachea varies with the part of the trachea being examined and also with the aging.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the subglottic and tracheal dimensions in females were comparatively and statistically less than males this is in agreement with most of the other studies [6,8,11]. We have observed that the trachea being a dynamic structure the shape of the trachea varies with the part of the trachea being examined and also with the aging.…”
Section: Resultssupporting
confidence: 93%
“…We could not find any references in literature which documented the measurements of the internal diameters of the subglottis. In Table 3 we have shown the comparison of the measurements of our study to earlier studies [3][4][5][6][7][8]. It is found that the average internal diameter in the south Indian population is less than that reported in literature.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…One method entails using radiographs to measure the tracheal width (5). However, the radiographic measurements accuracy was questioned due to inherent methodological issues such as variable magnification, rotation, inspiration, beam penetration, and intrinsic two dimensional nature (6) On the other hand, computed tomography (CT) proved to be a useful, fast and noninvasive method for obtaining tracheal measurements, with results comparable to the gold standard of bronchoscopy (7,8). The focus in the majority of the previously published studies was on measuring the growing trachea of the pediatric population (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The focus in the majority of the previously published studies was on measuring the growing trachea of the pediatric population (9,10). Only a few studies addressed tracheal morphometry using CT in adult subjects (6,11,12,13,14,15).Other methods include MRI or ultrasonography. However, the latter is operator dependant (7).…”
Section: Introductionmentioning
confidence: 99%